Numerical Analysis of Dynamics of Power End of Five-cylinder Reciprocating Fracturing Pump - Li Wei; Hong Lei (Jixie chuandong)
Using the mature theory of plane mechanism and SCILAB software,according to the structure and motion parameters of power end of fracturing pump,the dynamics model is established. The numerical analysis method is employed to obtain the force and motion curve in continuous operation. Besides,it provides important calculation basis for the stiffness,strength analysis and optimization design of the main components.